Production of the ρ(770)0 meson in pp and Pb-Pb collisions at sNN =2.76 TeV - Acharya, S.; Torales-Acosta, F.T.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; et al. (American Physical Society, 2019)
The production of the ( The particles have been reconstructed in the (770) 0 + -decay channel in the transverse-momentum (p T ) range 0.5-11 GeV/c. A centrality-dependent suppression of the ratio of the integrated yields 2(770) 0 /( + + -) is observed. The ratio decreases by 40% from pp to central Pb-Pb collisions. A study of the p T -differential 2( At higher momentum, particle ratios measured in heavy-ion and pp collisions are consistent. The observed suppression is very similar to that previously measured for the K * (892) 0 /K ratio and is consistent with EPOS3 predictions that may imply that rescattering in the hadronic phase is a dominant mechanism for the observed suppression.
Keywords: Physics; Hadron; Production (economics); Particle physics; Nuclear physics; https://purl.org/pe-repo/ocde/ford#1.03.03